The molecular basis of substrate specificity in FMN-dependent 2-hydroxyacid dehydrogenases : comparison of the flavocytochromes b2 from rhodotorula graminis and saccharomyces cerevisiae - Rosli Md. Illias; Reid, Graeme A.; Chapman, Stephen K.; Nadzarah Abd. Wahab; National Biotechnology Seminar (12th : 2000 : Lumut, Perak) (Skudai : Universiti Teknologi Malaysia, 2000)
42